Safety and effectiveness of acellular pertussis vaccination during pregnancy: a systematic review - Sabine Vygen-Bonnet; Wiebke Hellenbrand; Edeltraut Garbe; Rüdiger von Kries; Christian Bogdan; Ulrich Heininger; Marianne Röbl-Mathieu; Thomas Harder (BMC Infectious Diseases, 2020)
Abstract Background Infants < 3 months of age are at highest risk for developing severe complications after pertussis. The majority of pregnant women has low concentrations of pertussis-specific antibodies and thus newborns are insufficiently protected by maternally transferred antibodies. Acellular pertussis vaccination during pregnancy was recently implemented in various countries. Here, we assessed the evidence for safety and effectiveness of pertussis vaccination during pregnancy. Methods We searched Medline, Embase, and ClinicalTrials.gov from January 1st 2010 to January 10th 2019. We assessed risk of bias (ROB) using the Cochrane ROB tool and ROBINS-I. We evaluated the quality of evidence using the GRADE approach. Results We identified 1273 articles and included 22 studies (14 for safety; 8 for effectiveness), comprising 1.4 million pregnant women in safety studies and 855,546 mother-infant-pairs in effectiveness studies. No significant differences between vaccinated and unvaccinated women and their infants were observed for safety outcomes with the exception of fever and chorioamnionitis. Compared to no vaccination, three studies showed a significantly increased relative risk for the presence of the ICD-9 code for chorioamnionitis in electronic patient data after pertussis vaccination. However, no study reported an increased risk for clinical sequelae of chorioamnionitis after vaccination during pregnancy, such as preterm birth or neonatal intensive care unit admission. Vaccine effectiveness against pertussis in infants of immunized mothers ranged from 69 to 91% for pertussis prevention, from 91 to 94% for prevention of hospitalization and was 95% for prevention of death due to pertussis. Risk of bias was serious to critical for safety outcomes and moderate to serious for effectiveness outcomes. GRADE evidence quality was moderate to very low, depending on outcome. Conclusion Although an increased risk for a diagnosis of fever and chorioamnionitis was detected in pregnant women after pertussis vaccination, there was no association with a higher frequency of clinically relevant sequelae. Vaccine effectiveness for prevention of infant pertussis, hospitalization and death is high. Pertussis vaccination during pregnancy has an overall positive benefit-risk ratio. In view of the overall quality of available evidence ongoing surveillance of chorioamnionitis and its potential sequelae is recommended when pertussis vaccination in pregnancy is implemented. Trial registration PROSPERO CRD42018087814, CRD42018090357.